Evaluasi Kinerja Realisasi Anggaran Kecamatan Singkawang Tengah Tahun 2025 Berdasarkan Pendekatan Anggaran Berbasis Kinerja - Nurul Amanda; Elvira Mulya Nalien (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2025)
The problem studied is about the failure to achieve budget realization in Singkawang Tengah District, with a minimum target of 25%, thus indicating that the performance budget is not yet optimal. This study aims to evaluate budget realization in Singkawang Tengah District, with a focus on the Performance-Based Budget approach. The researcher utilized the Qualitative Descriptive research method, using secondary data from the first quarter Budget Realization Report (LRA). The analysis technique takes into account the percentage of budget absorption (input), the results or outputs of activities, and the performance impact (outcome). Through observation of the LRA document for the first quarter of March 2025, it reached only 15.46% of the total budget, finding that the realization is still far below the target. Where the ideal quarter is 25%. Furthermore, important expenditure items such as the provision of Employee Income Supplements (TPP) have not been realized. The results of the study indicate that the researcher's assessment is that the budget in Singkawang Tengah District focuses more on input or budget obtained from the community, and does not consider in depth how the results and impacts ultimately form output and outcomes. As a form of accountability for the use of public funds, a budget planning and reporting system is needed that focuses more on output and the impact of results.